Stalinism and Soviet Rail Transport, 1928–41 - Rees, E. A. author. aut Link
XIV, 307 p.
Keywords: This work provides an in-depth case-study of decision-making in the Soviet Union in the Stalin era. It focuses on the development of rail transport policy, upon which the entire economy as well as the country's defence were so crucially dependent. It analyses the role of institutional lobbies in shaping policy, and sheds new light on the Stakhanovite movement, and analyses for the first time the impact of the Great Purges on the railways. The work provides a critical examination of the adequacy of existing conceptualisations of the Stalinist state.